Penerapan Model ATIK Untuk Meningkatkan Literasi Numerasi Anak Usia Dini Melalui Media Menggambar di Pos PAUD Flamboyan I - Ika Puspitasari; Sri Watini (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2022)
This research is motivated by the lack of interest in early childhood in learning. This can be seen that there are still many early childhood children who are busy with themselves because during the learning process the teacher is only verbalistic without using the media. So that children do not understand what is explained by the teacher. The aim of this research is to prove whether the ATIK model in schools can increase interest in early childhood learning. This study uses a qualitative method with the type of case study. This study aims to describe the development of the ATIK model to improve PAUD in drawing competence in early childhood. The results of this study are that the ATIK model is able to increase interest in early childhood learning at school or at home. With the ATIK mode created by the PLAMBOYAN I PAUD institution, it makes children enthusiastic in learning. The ATIK model can also reduce early childhood playing online games, which so far, by playing online games, early childhood learning interest has decreased.